Healing Conversations on Race: The HEAL Model for Diverse Christian Communities - Vazquez, Veola E. (Journal of psychology and christianity, 2023)
In this article, the multi-racial team of authors—made up of biracial, White, and Black Christians—present the Healing Conversations on Race (HEAL) model for building racial unity among racially-different Christians within the Body of Christ. Both biblical and secular psychological conceptualizations of racial disunity are offered, followed by an integrated presentation of the key sources within the HEAL model that we believe can facilitate psychological and spiritual change within racially diverse, but often segregated, Christian communities. To build the HEAL intervention, the racially-diverse Christian co-authors draw from a variety of sources, including attachment theory, emotionally focused therapy (EFT), and the diversity literature (e.g., cultural humility) in secular psychology and the Bible and spiritual formation literature in Christianity. In doing so, the authors argue that proactively displaying humility, empathy, acceptance, and love, coupled with taking several key requisite steps (e.g., praying together; reciprocally expressing vulnerable, primary emotions; articulating and responding to each other’s concrete relational needs), during difficult conversations on race can help to develop more secure, Christlike attachment bonds in cross-racial relationships and solidify racial unity one relationship and one community at a time.